Active scanner control on paper machines. (December 2018) - Raunio, Jukka-Pekka; Ritala, Risto
Highlights: scanner path utilized as a manipulatable variable in paper machine cross-directional control. faster response to load disturbances. estimation of process noise and basis weight estimate uncertainty based on web-wide transmittance measurement. adaptive model between transmittance and basis weight. ABSTRACT: The cross-directional (CD) basis weight control on paper machines is improved by optimizing the path of the scanning measurement. The optimal path results from an LQG problem and depends on how the uncertainty of the present estimate of the basis weight and the intensity of process noise vary in CD. These factors are assessed by how accurately the CD basis weight estimate predicts the measured optical transmittance with a linear adaptive model on synchronized basis weight and transmittance data. Simulations on optimized scanner path in disturbance scenarios are presented, and the practical implementation of scanner control is discussed.